Digital Branding Strategy dalam Pemberdayaan Santripreneurship: Studi Intervensi pada Unit Usaha Kuliner 'Riyadh' di Pondok Pesantren Ar Riyadh: Digital Branding Strategy in Empowering Santripreneurship: An Intervention Study on the Culinary Business 'Riyadh' at Ar Riyadh Islamic Boarding School - Nurfaizana, Della Rulita; Zutiasari, Ika; Fuad, Muhammad (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The "Riyadh" Culinary Business Unit at Ar-Riyadh Islamic Boarding School in Pasuruan represents a tangible form of santripreneurship that faces critical challenges in branding and digital marketing. This community engagement program aims to empower the business unit through digital branding strategies, product packaging diversification, and the development of an e-catalog as a promotional tool. The methods used include training, mentoring, and quantitative-based evaluation. The results indicate a 78.7% increase in branding knowledge, a 317% growth in digital engagement, and a 37% increase in sales volume. Additionally, the product rebranding improved consumer perception by 92%. This program strengthens students' entrepreneurial competencies through technology and supports the achievement of SDG Goal 9 (Industry, Innovation, and Infrastructure). The project demonstrates that coaching-based digital branding is an effective strategy to enhance the competitiveness of pesantren-based MSMEs in the digital era.